Antiquities smuggling in the real and virtual world - Hashemi, Layla; Shelley, Louise (Abingdon, Oxon ; New York : Routledge, 2022)
"This book examines the illicit trade in antiquities, a trade which has increased massively following the destruction and looting of ancient Near Eastern sites in the Middle East. Focusing on the distribution networks for looted antiquities, especially the routes to the West, the book considers the dealers and facilitators who are key in getting the objects to market, explores the methods used including online marketplaces and social media sites, analyses demand and buyers, revealing that objects are often available at very affordable prices. It outlines the efforts of law enforcement agencies, including the military, and legal systems to contain the trade. Throughout the book highlights the difficulties of putting a stop to this illicit trade, particularly in a conflict region"--
Keywords: Archaeological thefts -- Middle East; Cultural property -- Protection -- Middle East; Classical antiquities -- Destruction and pillage -- Middle East; Classical antiquities thefts -- Middle East; Cultural property -- Protection; Black market -- Middle East; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Research